Eugenia alletiana (Myrtaceae), a new critically endangered species endemic to the island of Mauritius - Baider, Cláudia; Florens, F. B. Vincent (Phytotaxa, 2013)
Eugenia alletiana, a new endemic species from Mauritius, is described and its ecology and conservation is discussed. The morphological diagnostic features for Eugenia alletiana are chartaceous, discoloured leaves, very thin terminal branchlets, flowers solitary or in fascicles of 2–3 flowers, totally fused hypanthium without apical pore or calyptra, that encloses the numerous stamens (> 500) and petals before anthesis; seed enclosed in a woody endocarp with a lamellated outer surface. The species should be considered as Critically Endangered (CR) according to the Red List Criteria of the International Union for the Conservation of Nature. This assessment is based on the plant’s restricted distribution, very small population size, a habitat sustaining degradation by invasive alien plants and animals and predation of immature fruits and seeds by invasive alien monkeys and rats respectively leading to a weak regeneration.